UPAYA GURU DALAM MEMENUHI KEBUTUHAN DASAR PSIKOLOGIS SISWA DI SEKOLAH: SCOPING REVIEW - Muhammad Rahmadhani; Prasetyo Budi Widodo (Jurnal EMPATI, 2025)
Quality education is not only determined by academic factors, but also by the fulfillment of students' basic psychological needs. Basic psychological needs, consisting of autonomy, competence and relatedness, play an important role in students' well-being and motivation to learn. Teachers as educational agents have a strategic role in fulfilling these needs through various teaching strategies and interpersonal approaches. This study aims to systematically review the various efforts made by teachers in meeting students' basic psychological needs in primary and secondary schools. Using the scoping review method, this study analyzed 12 relevant journal articles from a total of 616 journal articles identified in the range of 2014-2024. The results of the review showed that there are various approaches such as interpersonal support, creating a supportive learning climate, and innovations in teaching methods, with the most commonly applied effort being autonomy support. The implications of this research point to the need for teachers to be able to implement more proactive strategies in supporting students' basic psychological needs, as well as the importance of training teachers on how these efforts can be effective strategies in improving student well-being. Keywords: basic psychological N\needs; school; students; teacher